2000
DOI: 10.1016/s0277-5387(00)00316-8
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium dithiophosphates: synthesis, X-ray crystal structure, spectroscopic and electrochemical properties

Abstract: The reactions of ammonium salts of dialkyldithiophosphate ligands, (RO) 2 PS 2 y NH 4 q (RsMe/Et), with Ru III Cl 3 P3H 2 O in methanol solvent and under N 2 atmosphere result in one-electron paramagnetic tris complexes {(RO) 2 PS 2 } 3 Ru III (1) in the solid state. The molecular structures of both complexes were determined by single-crystal X-ray diffraction. This shows the expected pseudo-octahedral geometry with reasonable strain due to the presence of a four-membered chelate ring. The reflectance spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Each four-membered RuS 2 P ring is nonplanar and contains a pair of nearly equal Ru-S bonds (Table 1) (Liu et al, 2005). The bond distances within the di-iso-proposaldithiophosphate ligands of the title complex agree well with those found in the analogous dimethyl-and diethyldithiophosphate complexes of ruthenium (Jain et al, 2000).…”
Section: S1 Commentsupporting
confidence: 54%
“…Each four-membered RuS 2 P ring is nonplanar and contains a pair of nearly equal Ru-S bonds (Table 1) (Liu et al, 2005). The bond distances within the di-iso-proposaldithiophosphate ligands of the title complex agree well with those found in the analogous dimethyl-and diethyldithiophosphate complexes of ruthenium (Jain et al, 2000).…”
Section: S1 Commentsupporting
confidence: 54%
“…The X-band EPR spectrum of 4 exhibits an isotropic signal with g = 2.088 with weak coupling to the I = 5/2 nuclear spin of 99,101Ru (29.8%) confirming an S = 1/2 spin-state,Figure 1 [19]. Lahiri and coworkers observed a similar isotropic EPR spectrum for a low spin Ru(III) complex with dialkylthiophosphate donors [20].…”
mentioning
confidence: 80%
“…metal-organic papers ORTEPII (Johnson, 1976) plot of the title compound with ellipsoids at the 50% probability level. The crystal structure of tris(dimethyldithiophosphato)ruthenium(III), (I), was originally described in the Cc space group (Jain et al, 2000). A check for additional symmetry by using the program PLATON (Spek, 1990) indicated that the correct space group for this structure is C2/c.…”
Section: Re®nementmentioning
confidence: 99%